2018
DOI: 10.1021/jacs.8b03517
|View full text |Cite
|
Sign up to set email alerts
|

Process-Tracing Study on the Postassembly Modification of Highly Stable Zirconium Metal–Organic Cages

Abstract: Metal-organic cages (MOCs) are discrete molecular assemblies formed by coordination bonds between metal nodes and organic ligands. The application of MOCs has been greatly limited due to their poor stability, especially in aqueous solutions. In this work, we thoroughly investigate the stability of several Zr-MOCs and reveal their excellent stability in aqueous solutions with acidic, neutral, and weak basic conditions. In addition, we present for the first time a process-tracing study on the postassembly modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
164
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(180 citation statements)
references
References 43 publications
5
164
3
Order By: Relevance
“…On the other hand, MOPs, which are stable under aqueous conditions, are highly desirable owing to extensive applications in aqueous environments, for example, in drug delivery and bioimaging . It is known that Zr‐MOFs are very stable in aqueous solutions; this could be ascribed to robust Zr−O bonds (Zr−O bond energy: 776 kJ mol −1 ) . Expanding upon research into Zr‐MOFs, some researchers have reported the synthesis of zirconium‐based MOPs, which are composed of trinuclear zirconium clusters and different carboxylate ligands .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MOPs, which are stable under aqueous conditions, are highly desirable owing to extensive applications in aqueous environments, for example, in drug delivery and bioimaging . It is known that Zr‐MOFs are very stable in aqueous solutions; this could be ascribed to robust Zr−O bonds (Zr−O bond energy: 776 kJ mol −1 ) . Expanding upon research into Zr‐MOFs, some researchers have reported the synthesis of zirconium‐based MOPs, which are composed of trinuclear zirconium clusters and different carboxylate ligands .…”
Section: Introductionmentioning
confidence: 99%
“…Yuan and co‐workers synthesized a series of tetrahedral Zr‐MOPs, the stabilities of which were systematically studied at different pH values. All of these polyhedra exhibited excellent stability in acidic, neutral, and even alkaline aqueous solution environments . In 2017, Choe and co‐workers first reported a robust amine‐functionalized Zr‐MOP (UMOP‐1‐NH 2 , which was also referred to as ZrT‐1‐NH 2 in other work) with a similar tetrahedral cage, and presented cross connections with organic molecules through the condensation of amines in UMOP‐1‐NH 2 and acyl chlorides .…”
Section: Introductionmentioning
confidence: 99%
“…The authors claimed this as the first example of covalent crosslinking between MOPs and, in fact, this could unite two distinct classes of materials, that is, MOPs and polymers, in a single composite. Recently, Zhao and co‐workers synthesized Zr‐MOCs (Figure a; MOC: metal–organic cage, synonymous to MOP) and studied their stability in aqueous media at different pH values . The cages were found to be exceptionally stable in neutral, acidic, and weakly basic aqueous environments (Figure b).…”
Section: Design Strategies To Construct Stable Porous Carboxylate Mopsmentioning
confidence: 99%
“…Now an iobium oxide-fluoride anion-pillared interpenetrated material ZU-62 (NbOFFIVE-2-Cu-i, NbOFFIVE = NbOF 5 2À ) is presented. [3] As one of the most produced chemicals,p ropylene is the widely used monomer for the production of the polymers, requires the polymer-grade purity (> 99.5 %w ith propyne and propadiene less than 1ppm). The multisite capture mechanism was revealed by modeling studies.…”
mentioning
confidence: 99%
“…[1] Especially towards the single component gas capture,t he amenable properties of the MOFs enable the possible design of customized pore structure for the specific molecule,j ust as the single molecule trap,w hich exhibiting excellent separation efficiencyf or various gas molecules. [3] As one of the most produced chemicals,p ropylene is the widely used monomer for the production of the polymers, requires the polymer-grade purity (> 99.5 %w ith propyne and propadiene less than 1ppm). Cascade removal based on the different adsorbents is still the dominant way,b ut is lowefficiency,complex, and high-cost.…”
mentioning
confidence: 99%